Seaweeds and its Applications: A Review (Global Journal of Computer Science and Technology, 2022)
Kelp is one of the main living assets of the sea Despite their wide applications in food and feed businesses they have acquired significance as restorative sources due to their high mending antimicrobial and antioxidative properties As a rich wellspring of important compound parts ocean growth is utilized in different businesses like beauty care products Fuel water treatment and so on Being a plant of remarkable construction and biochemical arrangement ocean growth could be utilized profoundly for its multi-useful properties as food energy medication and beauty care products The dispersion properties and wide use of kelp are examined exhaustively in this paper
Keywords: kelp; seaweeds; compound properties; living assets; business